2021
DOI: 10.1093/applin/amab058
|View full text |Cite
|
Sign up to set email alerts
|

Is It Time to Reconsider the ‘Gold Standard’ for Nativelikeness in ERP Studies on Grammatical Processing in a Second Language? A Critical Assessment Based on Qualitative Individual Differences

Abstract: In most event-related potential (ERP) studies on the second language (L2) processing, the native speaker (L1) control group’s grand average ERP pattern serves as the ‘gold standard’ that the L2 group has to reach to be labeled ‘native-like’. This relies on the assumption that the grand average is representative of all or most individuals in a group. Recent research, however, has shown that there can be considerable systematic qualitative variability between individuals even in coherent L1 samples, especially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…EEG findings on language processing have identified event-related potentials (ERPs) that are critical to language processing: a left anterior negativity (LAN) that peaks at around 250 to 300-millisecond (ms) post-stimulus onset, a positive deflection that peaks at roughly 600ms after stimulus presentation (i.e., the P600) and a negative deflection with a post-stimulus-onset latency of 400 to 500ms (i.e., the N400) [ 28 32 ]. Studies on L1 processing found that morphosyntactic oddity commonly elicited a LAN or an early left anterior negativity (ELAN, an early version of the LAN component that peaks at roughly 100ms post-stimulus onset) followed by a P600 response whereas semantic improbability regularly induced an N400 component (for a review, see [ 33 ]), and such observation was consistent across languages [ 34 39 ]. EEG studies on L2 morphosyntactic processing revealed that early stage L2 learners typically show either a meaning-oriented N400 or no robust brain reactions towards L2 morphosyntactic violations.…”
Section: Introductionmentioning
confidence: 93%
“…EEG findings on language processing have identified event-related potentials (ERPs) that are critical to language processing: a left anterior negativity (LAN) that peaks at around 250 to 300-millisecond (ms) post-stimulus onset, a positive deflection that peaks at roughly 600ms after stimulus presentation (i.e., the P600) and a negative deflection with a post-stimulus-onset latency of 400 to 500ms (i.e., the N400) [ 28 32 ]. Studies on L1 processing found that morphosyntactic oddity commonly elicited a LAN or an early left anterior negativity (ELAN, an early version of the LAN component that peaks at roughly 100ms post-stimulus onset) followed by a P600 response whereas semantic improbability regularly induced an N400 component (for a review, see [ 33 ]), and such observation was consistent across languages [ 34 39 ]. EEG studies on L2 morphosyntactic processing revealed that early stage L2 learners typically show either a meaning-oriented N400 or no robust brain reactions towards L2 morphosyntactic violations.…”
Section: Introductionmentioning
confidence: 93%
“…Revisit the Native-Speaker Benchmark for L2 Attainment Weber-Fox and Neville's (1996) seminal study and many subsequent neurocognitive studies on grammatical processing in L2 learners considered, explicitly or implicitly, native speaker performance as the ultimate goal and benchmark of L2 learning. Typically, as also reviewed above, researchers compared L2 learners' ERP patterns to native speaker ERP signatures to assess the extent to which L2 learners' performance was nativelike and whether the L2 learners' grand average waveform was qualitatively and quantitatively comparable to native speakers' grand average waveform (Freunberger et al, 2022).…”
Section: Apply Advanced Electroencephalography Techniques To Study L2...mentioning
confidence: 99%
“…As van Hell discussed, researchers have recently started acknowledging variability in L1 processing even within typical young speakers/readers, and such variability should be further investigated (Vaughn et al., 2019). We argue that the fields of both L1 and L2 processing would gain major advancements by deeply exploring individual variability in L1 processing (Freunberger et al., 2022). Research correlating L1 and L2 processing may reveal that L2 processing variability is at least partially explained by L1 processing variability.…”
mentioning
confidence: 99%
“…Correlation analyses of L1 with L2 processing would then be possible and certainly highly informative. Within‐participants designs also render comparisons with L1 speakers less needed, which would help move away from considering monolinguals as the gold standard (see Freunberger et al., 2022). Within‐participant designs are not always possible, for example, when researchers explore grammatical rules in the L2 that are absent in the L1.…”
mentioning
confidence: 99%
See 1 more Smart Citation